La retenue et l’excès : comment Miike Takashi a accédé au circuit des festivals internationaux - Tom Mes (Ebisu: Études Japonaises, 2022)
Japanese cinema has played a central role in film studies, but its canon of master directors and classic films obscures more than it reveals. Video was arguably cinema’s most transformative technological change since sound, but film scholars have long deemed it without interest and inferior to the benchmark of theatrical viewing, which has led to an incomplete understanding of recent Japanese cinema. Miike Takashi’s emergence in global film discourse challenges such accepted notions of cultural value. His use of seemingly opposing formal approaches of restraint and excess, plus his prolific output rooted in V-Cinema (direct-to-video release), met the expectations and gatekeeping of festival programmers and DVD distributors. This new insight into canon creation invites us to rethink “Japanese cinema”.